Positive electrode active material particle for lithium secondary battery, positive electrode for lithium secondary battery, and lithium secondary battery
Patent Information
- Application Number
- CN202180027977.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-04-14
- Filing Date
- 2021-04-12
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2041-04-12
AI Technical Summary
[0027]根据本发明,可以提供锂离子能够顺畅地迁移、能够使锂二次电池的电池特性提高的锂二次电池用正极活性物质颗粒、锂二次电池用正极以及锂二次电池。
Smart Images

Figure CN115398677B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to positive electrode active material particles for lithium secondary batteries, positive electrodes for lithium secondary batteries, and lithium secondary batteries.
[0002] This application claims priority based on Japanese Patent Application No. 2020-072300, filed in Japan on April 14, 2020, the contents of which are hereby incorporated. Background Technology
[0003] Lithium-ion rechargeable batteries are not only being used in small power sources such as mobile phones and laptops, but are also being adopted in medium- to large power sources such as automobiles and energy storage. Lithium metal composite oxides are being used as the positive electrode active material for lithium-ion rechargeable batteries.
[0004] Various attempts have been made to improve the battery characteristics of various secondary batteries, primarily lithium-ion batteries. For example, Patent Document 1 describes a material with good conductivity that can function as an electrode active material. Patent Document 1 also describes a composite oxide with good conductivity, exhibiting a small change in molar magnetic susceptibility over a temperature range of approximately 100–300 K.
[0005] Existing technical documents
[0006] Patent documents
[0007] Patent Document 1: JP-A-2005-145790 Summary of the Invention
[0008] The problem that the invention aims to solve
[0009] During the charging of a lithium-ion rechargeable battery, lithium ions are intercalated and deintercalated in the positive electrode active material. Conversely, during the discharging of a lithium-ion battery, lithium ions intercalate into the positive electrode active material. With the expanding applications of lithium-ion rechargeable batteries, there is a growing demand for smooth lithium ion migration and improved battery performance.
[0010] The present invention was made in view of the above circumstances, and its object is to provide positive electrode active material particles for lithium secondary batteries, positive electrode for lithium secondary batteries, and lithium secondary batteries, which enable lithium ions to migrate smoothly and improve the battery characteristics of lithium secondary batteries.
[0011] means for solving problems
[0012] This invention includes [1] to
[11] .
[0013] [1] A positive electrode active material particle for lithium secondary batteries, which is a positive electrode active material particle for lithium secondary batteries containing at least Li and Ni, wherein, when the volume magnetic susceptibility of a single particle of the positive electrode active material particle for lithium secondary batteries is determined for multiple particles, the modulus of the volume magnetic susceptibility in the range of 0.004 to 0.04 is greater than 0.004 and less than 0.012.
[0014] [2] The positive electrode active material particles for lithium secondary batteries according to [1], wherein the average value of the above-mentioned volume magnetic susceptibility is 0.001 to 0.3.
[0015] [3] The positive electrode active material particles for lithium secondary batteries according to [1] or [2], wherein the median value of the above-mentioned volume magnetic susceptibility is 0.00003 to 0.16.
[0016] [4] The positive electrode active material particles for lithium secondary batteries according to any one of [1] to [3], wherein the standard deviation of the above-mentioned volume magnetic susceptibility is 0.0018 to 0.4.
[0017] [5] The positive electrode active material particles for lithium secondary batteries according to any one of [1] to [4], wherein the average particle size based on the number of the positive electrode active material particles for lithium secondary batteries is 0.2 μm to 50 μm.
[0018] [6] The positive electrode active material particles for lithium secondary batteries according to any one of [1] to [5], wherein the median value of the particle size based on the number of the positive electrode active material particles for lithium secondary batteries is 0.2 μm to 40 μm.
[0019] [7] The positive electrode active material particles for lithium secondary batteries according to any one of [1] to [6], wherein the standard deviation of the particle size of the number of the positive electrode active material particles for lithium secondary batteries is 0.2 μm to 40 μm.
[0020] [8] The positive electrode active material particles for lithium secondary batteries according to any one of [1] to [7] contain a paramagnetic body or a diamagnetic body.
[0021] [9] The positive electrode active material particles for lithium secondary batteries according to any one of [1] to [8] are represented by the following composition formula (1).
[0022] Li[Li x (Ni (1-y-z-w) Co y Mn z M w ) 1-x O2 (1)
[0023] (In the formula, M is one or more elements selected from Cu, Ti, Mg, Al, W, B, Mo, Nb, Zn, Sn, Zr, Ga and V, satisfying -0.1≤x≤0.2, 0<y≤0.5, 0≤z≤0.8, 0≤w≤0.1 and y+z+w<1).
[0024]
[10] A positive electrode for a lithium secondary battery, comprising active material particles for a lithium secondary battery as described in any one of [1] to [9].
[0025]
[11] A lithium secondary battery having the positive electrode for a lithium secondary battery as described in
[10] .
[0026] Invention Effects
[0027] According to the present invention, positive electrode active material particles for lithium secondary batteries, positive electrode for lithium secondary batteries, and lithium secondary batteries can be provided, which enable lithium ions to migrate smoothly and improve the battery characteristics of lithium secondary batteries. Attached Figure Description
[0028] Figure 1A This is a schematic diagram illustrating an example of a lithium secondary battery.
[0029] Figure 1B This is a schematic diagram illustrating an example of a lithium secondary battery.
[0030] Figure 2 This is a schematic diagram illustrating the stacked structure of an all-solid-state lithium-ion secondary battery.
[0031] Figure 3 This is a schematic diagram showing the overall structure of an all-solid-state lithium-ion secondary battery. Detailed Implementation
[0032] <Definition>
[0033] In this specification, battery characteristics are evaluated using the first charge capacity and the first discharge capacity.
[0034] In this manual, the "initial charge capacity" and "initial discharge capacity" are measured by the following method.
[0035] First, the assembled coin-shaped lithium secondary battery is left to stand at room temperature for 10 hours, thereby allowing the electrolyte to fully impregnate the separator and the positive electrode agent layer.
[0036] Next, a constant current and constant voltage charging process was performed at room temperature for 5 hours, charging to 4.3V at a constant current of 1mA and then charging to 4.3V at a constant voltage. Then, a constant current discharge process was performed, discharging to 2.5V at a constant current of 1mA.
[0037] The charging capacity is measured, and the obtained value is "initial charge capacity" (mAh / g).
[0038] The discharge capacity was measured and the obtained value was called the "initial discharge capacity" (mAh / g).
[0039] In this specification, when the composition is “Ni / Co / Mn=85 / 10 / 5”, a first charge capacity of 226mAh / g or higher is considered to be large.
[0040] In this specification, when the composition is “Ni / Co / Al=88 / 9 / 3”, a first charge capacity of 221mAh / g or higher is considered to have a large first charge capacity.
[0041] In this specification, when the composition is “Ni / Co / Mn=85 / 10 / 5”, a first discharge capacity of 197mAh / g or higher is considered to have a large first discharge capacity.
[0042] In this specification, when the composition is “Ni / Co / Al=88 / 9 / 3”, a first discharge capacity of 192 mAh / g or higher is considered to have a large first discharge capacity.
[0043] In this specification, "volume magnetic susceptibility" refers to the magnetic susceptibility per unit volume of a single particle of positive electrode active material for lithium secondary batteries. Here, a single particle of positive electrode active material for lithium secondary batteries refers to a unit existing independently as a particle, and can be either a primary particle or a secondary particle, as described later.
[0044] In this specification, "magnetic susceptibility" is a physical property value that indicates the degree of magnetic polarization (magnetization) of a substance in a static magnetic field.
[0045] In this specification, "ferromagnetism" refers to the property of exhibiting strong magnetism in the same direction as an externally applied magnetic field. Materials exhibiting ferromagnetism are called ferromagnetic materials (also known as ferromagnets). Ferromagnetic materials possess the property of retaining strong magnetism even when the external magnetic field is zero. Examples of ferromagnetic materials include iron (Fe), cobalt (Co), and nickel (Ni). When a ferromagnetic material coexists with at least one of paramagnetic or diamagnetic materials, the overall ferromagnetism weakens, thereby easily increasing electrical conductivity.
[0046] In this specification, "paramagnetism" refers to the property of exhibiting weak magnetism in the same direction as an externally applied magnetic field. Materials exhibiting paramagnetism are called paramagnetic bodies (also known as paramagnetic materials). Paramagnetic bodies possess the property of becoming non-magnetic when the external magnetic field is zero. Examples of paramagnetic bodies include aluminum (Al), chromium (Cr), molybdenum (Mo), sodium (Na), titanium (Ti), and zirconium (Zr).
[0047] In this specification, "diamagnetism" refers to the property of exhibiting a very weak magnetism in the opposite direction when a strong external magnetic field is applied. Materials exhibiting diamagnetic properties are called diamagnetic bodies (also known as antimagnets). Diamagnetic bodies possess the property of having a magnetic field become zero when the external magnetic field is zero. Examples of diamagnetic bodies include gold (Au), silver (Ag), copper (Cu), zinc (Zn), silicon (Si), silicon carbide (SiC), aluminum oxide (Al₂O₃), silicon dioxide (SiO₂), silicon dioxide / alumina (SiO₂ / Al₂O₃), and titanium dioxide (TiO₂).
[0048] In this specification, "antiferromagnetism" refers to the property of not having a magnetic moment independent of an external magnetic field. Materials exhibiting antiferromagnetism are defined as antiferromagnetic materials. Examples of antiferromagnetic materials include manganese (Mn) and chromium (Cr).
[0049] In this embodiment, the metal composite compound is referred to as "MCC", the lithium metal composite oxide is referred to as "LiMO", and the cathode active material for lithium secondary batteries is referred to as "CAM".
[0050] In this embodiment, "positive electrode active material particles for lithium secondary batteries" is sometimes referred to as "CAM particles".
[0051] In one embodiment of this invention, CAM particles are formed from only one type of particles.
[0052] In one embodiment of this invention, CAM particles are formed only from secondary particles that are primary particle aggregates.
[0053] In one embodiment of this invention, CAM particles are composed of secondary particles that are primary particle aggregates and primary particles that exist independently of the secondary particles.
[0054] In one embodiment of this invention, the aggregate of CAM particles is powder.
[0055] "Ni" does not refer to nickel metal, but to nickel atoms. Similarly, "Co", "Li", "Na" and the like respectively refer to cobalt atoms, lithium atoms, sodium atoms and the like.
[0056] <CAM particle>
[0057] The CAM particle of the present embodiment contains at least Li and Ni.
[0058] In the present embodiment, the volume magnetic susceptibility of the entire single CAM particle for lithium secondary batteries is measured by the following method.
[0059] [Method for measuring volume magnetic susceptibility]
[0060] 75% glycerol is used as the medium for measurement. The measurement temperature is normal temperature (23°C). The volume magnetic susceptibility is calculated using the following formula. A magnetic field is applied to the CAM particles dispersed in the medium, and image analysis is performed on the moving CAM particles, whereby the volume magnetic susceptibility of the entire single CAM particle is measured.
[0061]
[0062] In the formula, X p is the volume magnetic susceptibility of the CAM particle for lithium secondary batteries. X m is the volume magnetic susceptibility of the medium. η is the viscosity. μ₀ is the vacuum permeability. B is the magnetic flux density. r is the radius of the CAM particle. v is the magnetophoretic velocity of the moving CAM particle.
[0063] The volume magnetic susceptibility can be measured using a magnetic susceptibility measurement device. As the magnetic susceptibility measurement device, for example, a particle magnetic susceptibility meter (KMG-001) manufactured by Yamato Scientific Co., Ltd. can be used.
[0064] <Mode Value>
[0065] The mode value is calculated using the respective volume magnetic susceptibilities obtained by measuring 1000 randomly selected CAM particles. In addition, as long as the number of CAM particles is 1000 or more, it can be considered that there is no significant error in the obtained mode value. Further, since the CAM particles are randomly selected, the 1000 selected CAM particles may be any of a mixture of primary particles and secondary particles, only primary particles, or only secondary particles.
[0066] In the present embodiment, the mode value in the range of 0.004 to 0.04 of the volume magnetic susceptibility is preferably 0.0041 or more, more preferably 0.0042 or more, and still more preferably 0.0043 or more.
[0067] The above-mentioned modulus value is less than 0.012, preferably less than 0.0119, more preferably less than 0.0118, and even more preferably less than 0.0117.
[0068] The upper and lower limits of the above modulus can be combined arbitrarily.
[0069] Examples of combinations of the upper and lower limits of the above modal values include 0.004 and above and less than 0.012, 0.0041 and above and less than 0.012, and 0.0042 and above and less than 0.012.
[0070] For the CAM particles of this embodiment with the aforementioned modulus within the aforementioned range, lithium ion insertion and extraction occur smoothly on the surface of the CAM particles. Therefore, the lithium ion conductivity is improved for the CAM particles of this embodiment. When using the CAM particles of this embodiment with the aforementioned modulus within the aforementioned range, the initial charge capacity and initial discharge capacity of the lithium secondary battery can be improved.
[0071] Average value of volume magnetic susceptibility
[0072] The average value was calculated using the volumetric magnetic susceptibility of each of at least 1000 CAM particles.
[0073] In this embodiment, the average value is preferably 0.001 or more, more preferably 0.002 or more, and even more preferably 0.003 or more.
[0074] The above average value is preferably 0.3 or less, more preferably 0.2 or less, and even more preferably 0.1 or less.
[0075] The upper and lower limits of the above average values can be combined arbitrarily.
[0076] Examples of combinations of the upper and lower limits of the above average values can be listed as 0.001 to 0.3, 0.002 to 0.2, and 0.003 to 0.1.
[0077] With regard to the CAM particles of this embodiment, which have an average value of 0.001 to 0.3, lithium ions can migrate smoothly, thereby improving the battery characteristics of lithium secondary batteries.
[0078] Median of volume magnetic susceptibility
[0079] The median was calculated using the volumetric magnetic susceptibility of each of at least 1000 CAM particles.
[0080] In this embodiment, the median value is preferably 0.00003 or more, more preferably 0.00004 or more, and even more preferably 0.00005 or more.
[0081] The median value is preferably 0.16 or less, more preferably 0.15 or less, and even more preferably 0.14 or less.
[0082] The upper and lower limits of the aforementioned median can be combined arbitrarily.
[0083] Examples of combinations include the median values of 0.00003–0.16, 0.00004–0.15, and 0.00005–0.14.
[0084] With respect to the CAM particles of this embodiment, which have a median value of 0.00003 to 0.16, lithium ions can migrate smoothly, thereby improving the battery characteristics of lithium secondary batteries.
[0085] Standard deviation of volumetric magnetic susceptibility
[0086] The standard deviation was calculated using the volumetric magnetic susceptibility of each of at least 1000 CAM particles.
[0087] The CAM particles of this embodiment preferably have a standard deviation of 0.0018 to 0.4 calculated by the above method. More preferably, the standard deviation is 0.0019 or more, and even more preferably 0.002 or more. Even more preferably, the standard deviation is 0.39 or less.
[0088] The upper and lower limits of the standard deviation can be combined arbitrarily. Examples of combinations of the upper and lower limits of the standard deviation include 0.0019 to 0.39 and 0.002 to 0.4.
[0089] The standard deviation mentioned above refers to the CAM particles in this embodiment where the deviation in the volumetric magnetic susceptibility of each CAM particle's surface is small. When using such CAM particles, the deviation in battery characteristics becomes smaller.
[0090] [Diamagnetic layer]
[0091] In this embodiment, the CAM particles are preferably particles having a diamagnetic layer on the surface of the LiMO particles. The diamagnetic layer may be formed in a form that covers the entire surface of the LiMO, or it may be formed in a form that covers a portion of the surface of the LiMO.
[0092] The diamagnetic layer is a layer with a higher aluminum content than LiMO. Specifically, the aluminum content is preferably 10-30% by mass relative to the total mass of the diamagnetic layer, more preferably 11-29% by mass. The diamagnetic layer may also contain non-diamagnetic elements. The proportion of non-diamagnetic elements is preferably 1-70% by mass relative to the total mass of the diamagnetic layer.
[0093] The LiMO in this embodiment contains at least Li and Ni. Since LiMO contains Ni, it exhibits ferromagnetism derived from Ni. By providing a diamagnetic layer on the surface of the ferromagnetic LiMO, lithium ions can smoothly migrate through the diamagnetic layer on the surface of the CAM particles.
[0094] Furthermore, in this embodiment, "having a diamagnetic layer on the surface of the LiMO particles" means that a diamagnetic layer exists on a portion or all of the surface of the LiMO. When the diamagnetic layer covers a portion of the surface of the LiMO, the diamagnetic layer is preferably distributed in a region of at least 0.1% of the surface of the LiMO, more preferably in a region of at least 0.2%.
[0095] The proportion of the LiMO surface coated with the diamagnetic layer can be calculated as follows: the coating ratio is obtained by dividing the weight increase of the diamagnetic element before and after sintering (based on ICP emission spectroscopy analysis) by the weight of LiMO.
[0096] In this embodiment, the CAM particles may have a diamagnetic layer on the surface of the primary particles of LiMO, or a diamagnetic layer on the surface of the secondary particles of LiMO.
[0097] Ferromagnetic particles with an antimagnetic layer have high lithium-ion conductivity.
[0098] (Layered structure)
[0099] In this embodiment, the crystal structure of LiMO is a layered structure, more preferably a hexagonal crystal structure or a monoclinic crystal structure. In this specification, "layered structure" refers to a crystal structure formed by stacked layers of lithium atoms, transition metal atoms, and oxygen atoms.
[0100] The hexagonal crystal structure belongs to the group selected from P3, P31, P32, R3, P-3, R-3, P312, P321, P3112, P3121, P3212, P3221, R32, P3m1, P31m, P3c1, P31c, R3m, R3c, P-31m, P-31c, P-3ml, P-3c1, R-3m, R-3c, P6, P61, P65. Any one of the following space groups: P62, P64, P63, P-6, P6 / m, P63 / m, P622, P6122, P6522, P6222, P6422, P6322, P6mm, P6cc, P63cm, P63mc, P-6m2, P-6c2, P-62m, P-62c, P6 / mmm, P6 / mcc, P63 / mcm, and P63 / mmc.
[0101] Furthermore, the crystal structure of the monoclinic form belongs to any one of the space groups selected from P2, P21, C2, Pm, Pc, Cm, Cc, P2 / m, P21 / m, C2 / m, P2 / c, P21 / c, and C2 / c.
[0102] Among them, in order to obtain lithium secondary batteries with high discharge capacity, the crystal structure is particularly preferred to be a hexagonal crystal structure belonging to space group R-3m or a monoclinic crystal structure belonging to C2 / m.
[0103] [Method for calculating particle size based on number]
[0104] In this embodiment, the average particle size based on the number of CAM particles is calculated using the image analysis tool of the particle size measuring device included in the volume magnetic susceptibility measuring device. The particle size of CAM measured by the volume magnetic susceptibility measuring device refers to the equivalent circle diameter of the particle.
[0105] Average particle size based on number of particles
[0106] The average particle size of the number reference obtained from the determination of at least 1000 CAM particles is preferably 0.2 μm to 50 μm.
[0107] The lower limits of the above average values can be listed as above 0.3 μm, above 0.4 μm, and above 0.5 μm. The upper limits of the above average values can be listed as below 40 μm, below 30 μm, and below 20 μm.
[0108] The upper and lower limits of the above average values can be combined arbitrarily.
[0109] Examples of combinations of the upper and lower limits of the aforementioned average values include 0.3μm to 40μm, 0.4μm to 30μm, and 0.5μm to 20μm. When the average value is between 0.2μm and 50μm, lithium ions can migrate smoothly, thus improving the battery characteristics of lithium-ion rechargeable batteries.
[0110] Median particle size based on number of particles
[0111] The median particle size of the number reference obtained from the determination of at least 1000 CAM particles is preferably 0.2 μm to 40 μm.
[0112] The lower limits of the above median values can be listed as above 0.3 μm, above 0.4 μm, and above 0.5 μm. The upper limits of the above median values can be listed as below 35 μm, below 30 μm, and below 20 μm.
[0113] The upper and lower limits of the aforementioned median can be combined arbitrarily.
[0114] Examples of combinations of the upper and lower limits of the aforementioned median values include 0.3μm to 35μm, 0.4μm to 30μm, and 0.5μm to 20μm. Within the median range of 0.2μm to 40μm, lithium ions can migrate smoothly, thus improving the battery characteristics of lithium-ion rechargeable batteries.
[0115] Standard deviation of particle size based on number of particles
[0116] The standard deviation of the particle size of the number reference obtained from the determination of at least 1000 CAM particles is preferably 0.2 μm to 40 μm.
[0117] The standard deviations mentioned above can be listed as ≥0.3μm, ≥0.4μm, and ≥0.5μm. The upper limits of the standard deviations mentioned above can be listed as ≤35μm, ≤30μm, and ≤20μm.
[0118] The upper and lower limits of the above standard deviation can be combined arbitrarily.
[0119] Examples of combinations of the upper and lower limits of the aforementioned standard deviation include 0.3μm to 35μm, 0.4μm to 30μm, and 0.5μm to 20μm. Within the range of 0.2μm to 40μm, lithium ions can migrate smoothly, thus improving the battery characteristics of lithium-ion rechargeable batteries.
[0120] [Composition]
[0121] The CAM particles in this embodiment are preferably represented by the following composition formula (1).
[0122] Li[Li x (Ni (1-y-z-w) Co y Mn z M w ) 1-x O2 (1)
[0123] (In the formula, M is one or more elements selected from Cu, Ti, Mg, Al, W, B, Mo, Nb, Zn, Sn, Zr, Ga and V, satisfying -0.1≤x≤0.2, 0<y≤0.5, 0≤z≤0.8, 0≤w≤0.1 and y+z+w<1.)
[0124] ·x
[0125] From the viewpoint of obtaining a lithium ion secondary battery with good cycle characteristics, x is preferably more than 0, more preferably 0.01 or more, and still more preferably 0.02 or more. In addition, from the viewpoint of obtaining a lithium ion secondary battery with a higher initial Coulombic efficiency, x is preferably 0.1 or less, more preferably 0.08 or less, and still more preferably 0.06 or less.
[0126] The upper limit value and lower limit value of x can be arbitrarily combined.
[0127] In the present embodiment, x is preferably 0<x≤0.2, and more preferably 0<x≤0.1.
[0128] ·y+z+w
[0129] From the viewpoint of obtaining a lithium secondary battery with high discharge capacity, y+z+w is preferably 0<y+z+w≤0.5, more preferably 0<y+z+w≤0.25, and still more preferably 0<y+z+w≤0.2.
[0130] ·y
[0131] From the viewpoint of obtaining a lithium ion secondary battery with low internal resistance, y is preferably 0.01 or more, more preferably 0.05 or more, and still more preferably 0.06 or more. In addition, from the viewpoint of obtaining a lithium ion secondary battery with high thermal stability, y is preferably 0.35 or less, and more preferably 0.3 or less.
[0132] The upper limit value and lower limit value of y can be arbitrarily combined.
[0133] In the present embodiment, y is preferably 0<y≤0.4.
[0134] ·z
[0135] From the viewpoint of obtaining a lithium secondary battery with high cycle characteristics, z is preferably 0.01 or more, more preferably 0.02 or more, and still more preferably 0.04 or more. In addition, from the viewpoint of obtaining a lithium ion secondary battery with high storage stability at high temperatures (for example, in an environment of 60°C), z is preferably 0.4 or less, more preferably 0.35 or less, and still more preferably 0.3 or less.
[0136] The upper limit value and lower limit value of z can be arbitrarily combined.
[0137] In the present embodiment, z is preferably 0.01≤z≤0.3.
[0138] ·Element M
[0139] Element M corresponds to a paramagnetic substance or a diamagnetic substance.
[0140] M in the above compositional formula (1) represents one or more elements selected from Cu, Ti, Mg, Al, W, B, Mo, Nb, Zn, Sn, Zr, Ga and V. Among them, the paramagnetic substances are Ti, Mg, Al, W, Mo, Nb, S, Zr and V. The diamagnetic substances are Cu, B, Zn and Ga.
[0141] In addition, from the viewpoint of making the average value of volume magnetic susceptibility fall within the desired range of the present embodiment, M in the compositional formula (1) is preferably one or more metals selected from Cu, Ti, Al, Mo, Zn and Zr.
[0142] ·W
[0143] w may be 0, but is preferably more than 0, more preferably 0.0005 or more, and still more preferably 0.001 or more. In addition, w is preferably 0.09 or less, more preferably 0.08 or less, and still more preferably 0.07 or less.
[0144] The upper limit value and the lower limit value of w can be arbitrarily combined.
[0145] For the present embodiment, w preferably satisfies 0.001 ≤ w ≤ 0.07.
[0146] <Method for producing CAM particles>
[0147] When producing the CAM particles of the present embodiment, it is preferred to first prepare an MCC that contains Ni as an essential metal element, which is a metal element other than Li, and an optional metal element, and then fire the MCC containing Ni and the optional metal element together with a lithium compound.
[0148] As the optional metal element, for example, one or more metal elements selected from Co, Mn, Fe, Cu, Mg, Mo, Zn, Sn, Ga and V are preferred.
[0149] The MCC containing Ni and the optional metal element is sometimes referred to as "precursor". As the precursor, a metal composite hydroxide containing an optional metal element or a metal composite oxide containing an optional metal element is preferred.
[0150] Hereinafter, an example of the method for producing CAM particles will be described by dividing it into a precursor production step and a CAM particle production step.
[0151] (Precursor production step: Example 1)
[0152] The precursor can be produced by a commonly known batch co-precipitation method or continuous co-precipitation method.
[0153] Examples of the precursor include metal composite hydroxides containing Ni, Co and Mn as metal elements.
[0154] The following describes in detail the manufacturing method using a precursor containing Ni, Co, and Mn as metallic elements.
[0155] First, a nickel salt solution, a cobalt salt solution, a manganese salt solution, and a complexing agent are reacted to produce a product made from Ni using a co-precipitation method, particularly the continuous method described in JP-A-2002-201028. (1-y-z) Co y Mn z (OH)2 (where 0 < y ≤ 0.5, 0 ≤ z ≤ 0.8, y + z < 1) represents the precursor.
[0156] There are no particular restrictions on the nickel salt used as the solute in the above nickel salt solution; for example, any one or more of nickel sulfate, nickel nitrate, nickel chloride, and nickel acetate can be used.
[0157] The cobalt salt used as the solute in the above cobalt salt solution can be, for example, any one or more of cobalt sulfate, cobalt nitrate, cobalt chloride, and cobalt acetate.
[0158] The manganese salt used as the solute in the above-mentioned manganese salt solution can be, for example, any one or more of manganese sulfate, manganese nitrate, manganese chloride, and manganese acetate.
[0159] The above metal salts are used in conjunction with the above Ni. (1-y-z) Co y Mn z The (OH)2 is used in a proportion corresponding to its composition. Additionally, water is used as a solvent.
[0160] Complexing agents are compounds that can form complexes with nickel, cobalt, and manganese ions in aqueous solution. Examples include ammonium ion donors, hydrazine, ethylenediaminetetraacetic acid, hypozinotriacetic acid, uracil diacetic acid, and glycine. Ammonium salts such as ammonium hydroxide, ammonium sulfate, ammonium chloride, ammonium carbonate, and ammonium fluoride can be listed as ammonium ion donors.
[0161] The amount of complexing agent contained in the mixture comprising nickel salt solution, cobalt salt solution, manganese salt solution and complexing agent is preferably a molar ratio of greater than 0 and less than 2.0 to the total number of moles of metal salts.
[0162] In the coprecipitation method, to adjust the pH of the mixture containing nickel salt solution, cobalt salt solution, manganese salt solution, and complexing agent, an alkaline aqueous solution is added to the mixture before the pH changes from alkaline to neutral. Sodium hydroxide or potassium hydroxide can be used as the alkaline aqueous solution.
[0163] Furthermore, the pH value in this specification is defined as the value measured when the temperature of the mixture is 40°C. The pH of the mixture was measured when the temperature of the mixture sampled from the reaction tank was 40°C.
[0164] When the temperature of the sampled mixture is below 40°C, the mixture is heated and the pH is measured when the temperature reaches 40°C.
[0165] When the temperature of the sampled mixture is above 40°C, the mixture is cooled and the pH is measured when it reaches 40°C.
[0166] Furthermore, during the reaction, the pH value in the reaction tank is controlled, for example, within the range of pH 9 to pH 13, preferably, for example, within the range of pH 11 to pH 13. When pH is set to pH 9 to pH 13, the average, median, and standard deviation of the particle size based on the number of CAM particles can be controlled within the above range.
[0167] When a complexing agent other than the aforementioned nickel salt solution, cobalt salt solution, and manganese salt solution is continuously supplied to the reaction tank, Ni, Co, and Mn react to generate Ni. (1-y-z) Co y Mn z (OH)2.
[0168] During the reaction, the temperature of the reaction tank is controlled, for example, within the range of 20°C to 80°C, preferably within the range of 30°C to 70°C.
[0169] The substances in the reaction tank are mixed by proper stirring.
[0170] Reactors used in continuous coprecipitation processes can be of the type that allow overflow to separate the resulting reaction precipitates.
[0171] The reaction vessel can be filled with an inert atmosphere. In an inert atmosphere, the aggregation of elements that are more easily oxidized than Ni can be suppressed, resulting in a homogeneous metal composite hydroxide containing Ni.
[0172] To control the oxidation state of the reaction precipitate, gas can be introduced into the reaction tank.
[0173] Methods for introducing gas include introducing a specified type of gas into the reaction tank or directly foaming the mixture.
[0174] The introduced gas can be an inert gas, an oxidizing gas, or a mixture of an inert gas and an oxidizing gas. Examples of inert gases include nitrogen, argon, and carbon dioxide. Examples of oxidizing gases include air or oxygen.
[0175] To control the oxidation state of the reaction precipitate, compounds that oxidize the reaction precipitate can also be added to the reaction tank.
[0176] As the compound used to oxidize the obtained reaction product, peroxides such as hydrogen peroxide, peroxide salts such as permanganate, perchlorate, hypochlorite, nitric acid, halogen, or ozone can be used.
[0177] To control the reduced state of the reaction precipitate, compounds that reduce the reaction precipitate can be added to the reaction tank.
[0178] As the compound that reduces the obtained reaction product, organic acids such as oxalic acid and formic acid, sulfites, or hydrazine can be used.
[0179] After the above reaction, the resulting precipitate was washed with water and then dried to obtain the precursor.
[0180] According to the above method, nickel cobalt manganese hydroxide, which is a nickel cobalt manganese composite compound, can be obtained as a precursor.
[0181] Alternatively, if impurities from the mixture remain when the reaction precipitate is washed with water alone, it can be washed with a weak acid solution or an alkaline solution. Examples of alkaline solutions used for washing include solutions containing sodium hydroxide or potassium hydroxide.
[0182] Furthermore, although the above examples produced nickel-cobalt-manganese composite hydroxides, nickel-cobalt-manganese composite oxides can also be prepared.
[0183] For example, nickel-cobalt-manganese composite oxides can be prepared by calcining nickel-cobalt-manganese composite hydroxides. Regarding the calcination time, the total time from the start of heating to reaching the desired temperature and then holding that temperature is preferably set to 1 to 30 hours. The heating rate for reaching the maximum holding temperature is preferably 180°C / hour or more, more preferably 200°C / hour or more, and particularly preferably 250°C / hour or more.
[0184] The maximum holding temperature in this specification refers to the highest temperature at which the atmosphere inside the firing furnace is held during the firing process; it refers to the firing temperature during the firing process. In the case of a main firing process that includes multiple heating processes, the maximum holding temperature refers to the highest temperature among all heating processes.
[0185] The heating rate in this manual is calculated from the time from the start of heating in the firing apparatus to the time until the maximum holding temperature is reached, and the temperature difference from the initial temperature at the start of heating in the firing furnace of the firing apparatus to the maximum holding temperature.
[0186] (Precursor manufacturing process: Example 2)
[0187] In this embodiment, the precursor can be a metal complex hydroxide containing Ni, Co, and Al as metal elements. In this case, the precursor can be manufactured by the same method as described above (precursor manufacturing process: Example 1), except that an aluminum salt solution is used instead of a manganese salt solution.
[0188] Aluminum salts used as solutes in aluminum salt solutions can include, for example, aluminum sulfate, sodium aluminate, etc.
[0189] (The manufacturing process of CAM particles)
[0190] The precursor obtained from the above process is dried and then mixed with a lithium compound.
[0191] In this embodiment, there are no particular limitations on the drying conditions of the metal composite oxide or metal composite hydroxide used as the precursor. The drying conditions can be any of the conditions described in 1) to 3) below.
[0192] 1) Conditions under which metal composite oxides or metal composite hydroxides are not oxidized or reduced. Specifically, these are the drying conditions under which oxides maintain their oxide state and the drying conditions under which hydroxides maintain their hydroxide state.
[0193] 2) Conditions for the oxidation of metal complex hydroxides. Specifically, these are the drying conditions under which hydroxides are oxidized to oxides.
[0194] 3) Conditions for the reduction of metal complex oxides. Specifically, these are the drying conditions under which oxides are reduced to hydroxides.
[0195] To obtain conditions that prevent oxidation or reduction, the atmosphere used during drying only needs to be composed of inert gases such as nitrogen, helium, and argon.
[0196] To obtain the conditions for the hydroxide to be oxidized, the drying atmosphere only needs to be oxygen or air.
[0197] In addition, to obtain the conditions for the reduction of metal composite oxides, it is sufficient to use reducing agents such as hydrazine or sodium sulfite during drying in an inert gas atmosphere.
[0198] After drying, metal composite oxides or metal composite hydroxides can also be appropriately graded.
[0199] LiMO can be obtained by calcining a mixture containing a precursor and a lithium compound.
[0200] As a mixture to be fired, mixture 1 or mixture 2 can be listed below.
[0201] • Mixture 1: A mixture of precursor and lithium compound.
[0202] • Mixture 2: A mixture of precursor, lithium compound and inactive flux.
[0203] As a lithium compound, any one or a combination of two or more of lithium carbonate, lithium nitrate, lithium acetate, lithium hydroxide, lithium hydroxide hydrate, and lithium oxide can be used.
[0204] A diamagnetic material is added to either mixture 1 or mixture 2, and the mixture is then sintered in a state where the diamagnetic material is in contact with mixture 1 or mixture 2. This allows the production of CAM particles having a diamagnetic layer on the surface of ferromagnetic particles.
[0205] As a diamagnetic medium, alumina media and aluminum media can be used. The alumina media contains at least 99% alumina by mass relative to its total mass, and contains one or more elements selected from Si, K, Na, and Fe as impurities. The aluminum media contains at least 99% Al by mass relative to its total mass, and contains one or more elements selected from Si, K, Na, and Fe as impurities. The median particle size of both the aluminum and aluminum media is 2–2.2 mm based on volume. The median particle size based on volume is determined by sieving using a vibrating screen device.
[0206] The amount of diamagnetic material added is preferably 1 to 10% by mass relative to the total mass of mixture 1 or mixture 2, and more preferably 2 to 9% by mass. By adjusting the amount of diamagnetic material added, the mode, average, median, and standard deviation of the volume magnetic susceptibility of the CAM particles can be adjusted to the range of this embodiment.
[0207] The inert flux used in this embodiment is not particularly limited as long as it does not readily react with the mixture during firing. In this embodiment, examples include fluorides, chlorides, carbonates, sulfates, nitrates, phosphates, hydroxides, molybdates, and tungstates of one or more elements selected from Na, K, Rb, Cs, Ca, Mg, Sr, and Ba (hereinafter referred to as "A"). Specifically, the compounds described in JP6734491B are examples.
[0208] In this embodiment, two or more of these inactive fluxes may be used. When two or more are used, the overall melting point of the inactive fluxes may sometimes decrease.
[0209] In addition, among these inactive fluxes, one or more salts selected from the carbonate, sulfate and chloride of A are preferred.
[0210] In this embodiment, it is sufficient to appropriately select the amount of inactive flux present during firing. For example, the amount of inactive flux present during firing is preferably 0.1 parts by mass or more, more preferably 1 part by mass or more, relative to 100 parts by mass of the lithium compound. Furthermore, when it is necessary to promote CAM particle growth, inactive fluxes other than those listed above can be used. Examples of inactive fluxes used in this case include ammonium salts such as NH4Cl and NH4F.
[0211] The lithium compounds and precursors mentioned above are used considering the composition ratio of the final target product. For example, in the case of using nickel-cobalt-manganese composite hydroxides, the lithium compound and the metal composite hydroxide are used in combination with Li[Li x (Ni (1-y-z) Co y Mn z ) 1-x The composition ratio of O2 (where -0.1≤x≤0.2, 0<y≤0.5, 0≤z≤0.8, y+z+w<1) is used accordingly. Furthermore, for CAM particles, which are the final target material, in the case of Li excess (containing a molar ratio exceeding 1), they are mixed in a ratio where the molar ratio of Li contained in the lithium compound to the metal element contained in the metal composite hydroxide is greater than 1.
[0212] By calcining mixture 1 or mixture 2, CAM particles containing Li and Ni can be obtained. Furthermore, the calcination is carried out using dry air, an oxygen atmosphere, or an inert atmosphere, depending on the desired composition.
[0213] The firing process can be a single firing or it can include multiple firing stages.
[0214] In cases involving multiple firing stages, the firing process at the highest temperature is referred to as the main firing. A pre-firing at a lower temperature than the main firing can also be performed before the main firing. Furthermore, a post-firing at a lower temperature than the main firing can be performed after the main firing.
[0215] Regarding the firing temperature (maximum holding temperature) for the main firing, from the viewpoint of promoting CAM particle growth, 600°C or higher is preferred, 700°C or higher is more preferred, and 800°C or higher is particularly preferred. Furthermore, from the viewpoint of maintaining the strength of the CAM particles, 1200°C or lower is preferred, 1100°C or lower is more preferred, and 1000°C or lower is particularly preferred.
[0216] The upper and lower limits of the maximum holding temperature for the main firing can be combined arbitrarily.
[0217] Examples of combinations include 600℃~1200℃, 700℃~1100℃, and 800℃~1000℃. When the maximum holding temperature for the main firing is 600℃~1200℃ and the firing atmosphere is oxygen, the average, median, and standard deviation of the particle size based on the number of CAM particles can be controlled within the aforementioned ranges.
[0218] The firing temperature for pre-firing or post-firing only needs to be lower than the firing temperature for the main firing, for example, a range of 350℃ to 700℃ can be listed.
[0219] The holding temperature during firing can be adjusted appropriately according to the type, amount, or amount of transition metal element used.
[0220] Furthermore, the holding time at the aforementioned temperature can range from 0.1 hours to 20 hours, preferably from 0.5 hours to 10 hours. The heating rate up to the aforementioned holding temperature is typically 50°C / hour to 400°C / hour, and the cooling rate from the aforementioned holding temperature to room temperature is typically 10°C / hour to 400°C / hour. Additionally, the firing atmosphere can be atmospheric gas, oxygen, nitrogen, argon, or a mixture thereof.
[0221] After calcination, the calcined material is washed and then dried to obtain CAM particles containing Li and Ni.
[0222] As a cleaning solution, pure water or an alkaline solution can be used.
[0223] After cleaning, it is preferable to remove any residual cleaning solution by drying.
[0224] Through the above processes, CAM particles containing lithium and nickel can be obtained.
[0225] CAM particles are properly crushed and graded. When crushing with a disc mill, the average, median, and standard deviation of the particle size based on the number of CAM particles can be controlled within the above-mentioned range.
[0226] In this embodiment, the performance of CAM particles can be evaluated by the first discharge capacity and the first charge capacity obtained by the following method.
[0227] [Fabrication of the positive electrode for lithium secondary batteries]
[0228] A paste-like positive electrode mixture was prepared by adding CAM particles, conductive material (acetylene black), and binder (PVdF) in a mass ratio of 92:5:3 (CAM particles: conductive material: binder) and kneading. N-methyl-2-pyrrolidone was used as the organic solvent in the preparation of the positive electrode mixture.
[0229] [Making a Lithium-ion Secondary Battery (Coin-type Half-cell)]
[0230] Perform the following operations inside a glove box under an argon atmosphere.
[0231] The positive electrode for a lithium secondary battery, prepared according to the [Preparation of Positive Electrode for Lithium Secondary Batteries], is placed with its aluminum foil side down on the lower cover of a component for a coin-type battery R2032 (manufactured by Hosen Co., Ltd.), and a separator (a porous polyethylene membrane) is placed on top of it. 300 μL of electrolyte is then injected.
[0232] The electrolyte is prepared by dissolving LiPF6 in a 30:35:35 (volume ratio) mixture of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate at a ratio of 1.0 mol / L.
[0233] Next, lithium metal is used as the negative electrode, and the negative electrode is placed on the upper side of the laminated membrane separator. The top cover is then placed on the membrane through a gasket, and the two are riveted together using a riveting machine to produce a lithium secondary battery (coin-type half-cell R2032. Hereinafter sometimes referred to as "half-cell").
[0234] [Charge / Discharge Evaluation: Initial Charge Capacity and Initial Discharge Capacity]
[0235] Using a coin-type lithium secondary battery, as described in the above-described methods for measuring "first charge capacity" and "first discharge capacity", the first charge capacity and first discharge capacity can be measured and evaluated.
[0236] <Lithium secondary batteries>
[0237] Next, while explaining the structure of the lithium secondary battery, a lithium secondary battery using CAM particles manufactured in this embodiment as the positive electrode of the CAM of the lithium secondary battery and a lithium secondary battery having the positive electrode will be explained.
[0238] The CAM particles for lithium secondary batteries in this embodiment are preferably formed from the CAM particles for lithium secondary batteries described in this embodiment, but may contain other components without impairing the effects of the present invention. For example, the content ratio of the CAM particles for lithium secondary batteries in this embodiment relative to the total mass (100% by mass) of the CAM particles for lithium secondary batteries is preferably 70-99% by mass, more preferably 80-98% by mass.
[0239] Furthermore, a positive electrode (hereinafter sometimes referred to as positive electrode) for a lithium secondary battery suitable for using the CAM of this embodiment will be described.
[0240] Furthermore, a lithium secondary battery suitable for use as a positive electrode will be explained.
[0241] An example of a lithium secondary battery according to this embodiment has a positive electrode and a negative electrode, a separator sandwiched between the positive and negative electrodes, and an electrolyte disposed between the positive and negative electrodes.
[0242] Figure 1A , Figure 1B This is a schematic diagram illustrating an example of the lithium secondary battery of this embodiment. The cylindrical lithium secondary battery 10 of this embodiment is manufactured as follows.
[0243] First, such as Figure 1A As shown, an electrode group 4 is formed by stacking and winding a pair of strip-shaped diaphragms 1, a strip-shaped positive electrode 2 with a positive electrode lead 21 at one end, and a strip-shaped negative electrode 3 with a negative electrode lead 31 at one end in the order of diaphragm 1, positive electrode 2, diaphragm 1, and negative electrode 3.
[0244] Next, as Figure 1B As shown, after the battery can 5 houses the electrode group 4 and an insulator (not shown), the bottom of the can is sealed, allowing the electrolyte 6 to be immersed in the electrode group 4, with the electrolyte positioned between the positive electrode 2 and the negative electrode 3. Then, the upper part of the battery can 5 is sealed with a top insulator 7 and a sealing body 8, thereby manufacturing a lithium secondary battery 10.
[0245] As for the shape of the electrode group 4, for example, a columnar shape such as a circle, ellipse, rectangle or a rectangle with rounded corners can be listed when the cross-sectional shape of the electrode group 4 is cut in the vertical direction relative to the winding axis.
[0246] Furthermore, the shape of the lithium secondary battery having such an electrode group 4 can be adopted from the shapes specified in the International Electrotechnical Commission (IEC) battery standards IEC 60086 or JIS C 8500. For example, cylindrical, square, and other shapes can be listed.
[0247] Furthermore, lithium secondary batteries are not limited to the wound type structure described above; they can also be stacked types formed by repeatedly overlapping a positive electrode, a separator, a negative electrode, and a separator. Examples of stacked lithium secondary batteries include so-called coin-type batteries, button-type batteries, or paper-type (or sheet-type) batteries.
[0248] The following sections will explain each component in turn.
[0249] (positive electrode)
[0250] The positive electrode of this embodiment can be manufactured by first preparing a positive electrode mixture containing CAM, conductive material and binder and then loading the positive electrode mixture onto the positive electrode current collector.
[0251] (Conductive materials)
[0252] As the conductive material of the positive electrode in this embodiment, carbon materials can be used. Examples of carbon materials include graphite powder, carbon black (e.g., acetylene black), and fibrous carbon materials.
[0253] The proportion of conductive material in the positive electrode mixture is preferably 5 to 20 parts by mass relative to 100 parts by mass of CAM.
[0254] (Adhesive)
[0255] Thermoplastic resins can be used as binders for the positive electrode. Examples of such thermoplastic resins include: polyimide resins; fluorinated resins such as polyvinylidene fluoride (hereinafter sometimes referred to as PVdF) and polytetrafluoroethylene; polyolefin resins such as polyethylene and polypropylene; and resins described in WO2019 / 098384A1 or US2020 / 0274158A1.
[0256] These thermoplastic resins can be used in combination of two or more. By using fluorinated resin and polyolefin resin as binders and making the ratio of fluorinated resin to the positive electrode binder 1% to 10% by mass and the ratio of polyolefin resin to the positive electrode binder 0.1% to 2% by mass, a positive electrode binder with high adhesion to the positive electrode current collector and high bonding strength within the positive electrode binder can be obtained.
[0257] (Positive current collector)
[0258] As the positive current collector of the positive electrode, a strip-shaped component made of metal materials such as Al, Ni or stainless steel can be used.
[0259] As a method for loading a positive electrode compound onto a positive electrode current collector, the following methods can be listed: gelatinizing the positive electrode compound using an organic solvent, coating the resulting positive electrode compound paste onto at least one side of the positive electrode current collector and drying it, and pressing it to fix it.
[0260] When gelatinizing the positive electrode mixture, the organic solvents that can be used include: N-methyl-2-pyrrolidone (hereinafter sometimes referred to as NMP), the solvents described in WO2019 / 098384A1 or US2020 / 0274158A1.
[0261] Methods for coating the positive electrode paste onto the positive electrode current collector include, for example, slit coating, screen coating, curtain coating, blade coating, gravure coating and electrostatic spraying.
[0262] The positive electrode can be manufactured using the methods listed above.
[0263] (negative electrode)
[0264] The negative electrode of a lithium secondary battery only needs to be able to dope and dedope lithium ions at a lower potential than the positive electrode. Examples include electrodes consisting of a negative electrode compound containing negative electrode active material supported on a negative electrode current collector and electrodes consisting solely of negative electrode active material.
[0265] (Negative electrode active material)
[0266] The negative electrode active materials that can be used as negative electrodes include carbon materials, chalcogenides (oxides, sulfides, etc.), nitrides, metals or alloys, and materials that can be doped and dedoped with lithium ions at a lower potential than that of the positive electrode.
[0267] Carbon materials that can be used as negative electrode active materials include: natural or artificial graphite, coke, carbon black, carbon fibers, and sintered organic polymer compounds.
[0268] Oxides that can be used as negative electrode active materials include: SiO2, SiO, etc. (SiO2 is an oxide with the formula SiO2). x (Here, x is a positive real number) represents silicon oxides; SnO2, SnO, etc., are derived from the formula SnO x (Here, x is a positive real number) represents tin oxides; and Li4Ti5O 12 LiVO2 and other composite metal oxides containing lithium and titanium or vanadium.
[0269] Furthermore, examples of metals that can be used as negative electrode active materials include lithium metal, silicon metal, and tin metal. Materials described in WO2019 / 098384A1 or US2020 / 0274158A1 can also be used as negative electrode active materials.
[0270] These metals and alloys, after being processed into foil, are primarily used as electrodes on their own.
[0271] Among the aforementioned negative electrode active materials, carbon materials with graphite as the main component, such as natural graphite or artificial graphite, are preferred because the potential of the negative electrode hardly changes from an uncharged state to a fully charged state during charging (good potential flatness), the average discharge potential is low, and the capacity retention rate during repeated charge and discharge (good cycle characteristics). The shape of the carbon material can be any shape, such as flakes like natural graphite, spheres like mesophase carbon microspheres, fibers like graphitized carbon fibers, or aggregates of micropowders.
[0272] The aforementioned negative electrode mixture may contain a binder as needed. Examples of binders include thermoplastic resins, specifically PVdF, thermoplastic polyimide, carboxymethyl cellulose (hereinafter sometimes referred to as CMC), styrene-butadiene rubber (hereinafter sometimes referred to as SBR), polyethylene, and polypropylene.
[0273] (Negative current collector)
[0274] As a negative electrode current collector, examples include strip-shaped components made of metallic materials such as Cu, Ni, and stainless steel.
[0275] As for methods of loading the negative electrode mixture onto such a negative electrode current collector, similar to those for the positive electrode, the following methods can be listed: a method based on pressure molding, a method of gelatinizing and coating the mixture with a solvent or the like onto the negative electrode current collector, and then pressing and bonding it after drying.
[0276] (Septum)
[0277] As a separator in a lithium-ion secondary battery, materials such as porous membranes, nonwoven fabrics, or woven fabrics formed from polyolefin resins such as polyethylene and polypropylene, fluorinated resins, or nitrogen-containing aromatic polymers can be used. Furthermore, two or more of these materials can be used to form the separator, or these materials can be layered to form the separator. Alternatively, the separators described in JP-A-2000-030686 or US20090111025A1 can also be used.
[0278] (electrolyte)
[0279] The electrolyte in the lithium secondary battery of this embodiment contains an electrolyte and an organic solvent.
[0280] Lithium salts such as LiClO4 and LiPF6 can be used as electrolytes in the electrolyte solution, or mixtures of two or more of them can be used. Alternatively, the electrolytes described in WO2019 / 098384A1 or US2020 / 0274158A1 can also be used.
[0281] In addition, as an organic solvent contained in the above-mentioned electrolyte, carbonates such as propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate can be used. Furthermore, as an organic solvent contained in the electrolyte, the organic solvents described in WO2019 / 098384A1 or US2020 / 0274158A1 can be used.
[0282] As organic solvents, it is preferable to use a mixture of two or more of them, more preferably a mixed solvent of cyclic carbonates and non-cyclic carbonates and a mixed solvent of cyclic carbonates and ethers.
[0283] Furthermore, as the electrolyte, to improve the safety of the resulting lithium secondary battery, it is preferable to use an electrolyte containing a fluorinated lithium salt such as LiPF6 and an organic solvent with fluorine substituents. The electrolyte and organic solvent contained in the electrolyte may also be those described in WO2019 / 098384A1 or US2020 / 0274158A1.
[0284] The positive electrode with the above-described structure, having CAM particles of the aforementioned structure, can improve the charging and discharging capacity of lithium secondary batteries.
[0285] Furthermore, lithium secondary batteries with the above-described configuration, having the aforementioned positive electrode, become secondary batteries with large charging and discharging capacities.
[0286] All-solid-state lithium-ion secondary batteries
[0287] Next, while explaining the structure of the all-solid-state lithium secondary battery, we will also explain the positive electrode of the all-solid-state lithium-ion secondary battery that uses CAM particles for lithium secondary batteries manufactured in this embodiment as the positive electrode of the CAM, and the all-solid-state lithium-ion secondary battery having the positive electrode.
[0288] Figure 2 , 3 This is a schematic diagram illustrating an example of an all-solid-state lithium secondary battery. Figure 2 This is a schematic diagram illustrating the stacked structure of an all-solid-state lithium-ion secondary battery. Figure 3 This is a schematic diagram showing the overall structure of an all-solid-state lithium-ion secondary battery.
[0289] The all-solid-state lithium secondary battery 1000 has a laminate 100 and an outer casing 200 that houses the laminate 100. The laminate 100 has a positive electrode 110, a negative electrode 120, and a solid electrolyte layer 130. Alternatively, the all-solid-state lithium secondary battery 1000 can be a bipolar structure formed by distributing a current collector (CAM) and a negative electrode active material on both sides of the current collector. A specific example of a bipolar structure is the structure described in JP-A-2004-95400.
[0290] The materials that make up each component will be described later.
[0291] The laminate 100 may have an external terminal 113 connected to the positive current collector 112 and an external terminal 123 connected to the negative current collector 122. In addition, the all-solid-state lithium secondary battery 1000 may have a separator between the positive electrode 110 and the negative electrode 120.
[0292] Regarding the laminate 100, the positive electrode 110 and the negative electrode 120 sandwich the solid electrolyte layer 130 in a manner that prevents them from short-circuiting each other. In addition, the all-solid-state lithium-ion secondary battery 1000 may also have a separator between the positive electrode 110 and the negative electrode 120, similar to that used in conventional liquid lithium-ion secondary batteries, to prevent the positive electrode 110 and the negative electrode 120 from short-circuiting.
[0293] The all-solid-state lithium secondary battery 1000 also includes an insulator (not shown) that insulates the laminate 100 from the outer casing 200, and a sealing body (not shown) that seals the opening 200a of the outer casing 200.
[0294] The outer casing 200 can be a container made of a highly corrosion-resistant metal material such as aluminum, stainless steel, or nickel-plated steel. Alternatively, the outer casing 200 can also be a bag-shaped container made by processing a laminated film on at least one side with a corrosion-resistant finish.
[0295] Regarding the shape of the all-solid-state lithium secondary battery 1000, for example, it can be coin-shaped, button-shaped, paper-shaped (or sheet-shaped), cylindrical, square, or laminated (bag-shaped) and other shapes.
[0296] Although the all-solid-state lithium secondary battery 1000 is illustrated as having a single stack 100, it is not limited thereto. The all-solid-state lithium secondary battery 1000 may also be configured such that the stack 100 is a single cell and multiple single cells (stack 100) are sealed inside the outer casing 200.
[0297] The following sections will explain each component in turn.
[0298] (positive electrode)
[0299] The positive electrode 110 has a positive electrode active material layer 111 and a positive electrode current collector 112.
[0300] The positive electrode active material layer 111 comprises CAM particles as described in one aspect of the present invention. Alternatively, the positive electrode active material layer 111 may also comprise a solid electrolyte, a conductive material, and a binder.
[0301] (Solid electrolyte)
[0302] The solid electrolyte that can be used as the positive electrode active material layer 111 can be a known solid electrolyte that has lithium-ion conductivity and can be used in all-solid-state batteries. Examples of such solid electrolytes include inorganic electrolytes and organic electrolytes. Examples of inorganic electrolytes include oxide-based solid electrolytes, sulfide-based solid electrolytes, and hydride-based solid electrolytes. Examples of organic electrolytes include polymer-based solid electrolytes. Examples of compounds described in WO2020 / 208872A1, US2016 / 0233510A1, US2012 / 0251871A1, and US2018 / 0159169A1 can be cited as examples.
[0303] (Oxide-based solid electrolyte)
[0304] Examples of oxide-based solid electrolytes include perovskite oxides, nASICON oxides, LISICON oxides, and garnet oxides. Specific examples of these oxides include the compounds described in WO2020 / 208872A1, US2016 / 0233510A1, and US2020 / 0259213A1, such as the following compounds.
[0305] As a garnet-type oxide, Li7La3Zr2O can be listed as an example. 12 Li-La-Zr oxides such as (LLZ) are examples of such oxides.
[0306] Oxide-based solid electrolytes can be crystalline or amorphous (non-crystalline) materials.
[0307] (Sulfide-based solid electrolyte)
[0308] As sulfide-based solid electrolytes, the following can be listed: Li₂S-P₂S₅ compounds, Li₂S-SiS₂ compounds, Li₂S-GeS₂ compounds, Li₂S-B₂S₃ compounds, Li₂S-P₂S₃ compounds, LiI-Si₂S-P₂S₅ compounds, LiI-Li₂S-P₂O₅ compounds, LiI-Li₃PO₄-P₂S₅ compounds, and Li 10 GeP2S 12 wait.
[0309] Furthermore, in this specification, the term "system compound" for sulfide-based solid electrolytes is used as a general term for solid electrolytes that primarily contain raw materials such as "Li2S" and "P2S5" as described before "system compound". For example, the Li2S-P2S5 system compound includes Li2S and P2S5, and further includes solid electrolytes containing other raw materials. The proportion of Li2S contained in the Li2S-P2S5 system compound is, for example, 50 to 90% by mass relative to the total Li2S-P2S5 system compound. The proportion of P2S5 contained in the Li2S-P2S5 system compound is, for example, 10 to 50% by mass relative to the total Li2S-P2S5 system compound. In addition, the proportion of other raw materials contained in the Li2S-P2S5 system compound is, for example, 0 to 30% by mass relative to the total Li2S-P2S5 system compound. Furthermore, the Li2S-P2S5 system compound also includes solid electrolytes with different mixing ratios of Li2S and P2S5.
[0310] As compounds in the Li2S-P2S5 series, examples include Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, and Li2S-P2S5-LiI-LiBr.
[0311] As Li₂S-SiS₂ compounds, examples include Li₂S-SiS₂, Li₂S-SiS₂-LiI, and Li₂S-SiS₂-LiB. r , Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-SiS2-P2S5-LiCl, etc.
[0312] Examples of Li2S-GeS2 compounds include Li2S-GeS2 and Li2S-GeS2-P2S5.
[0313] Sulfide-based solid electrolytes can be crystalline or amorphous (non-crystalline) materials.
[0314] Two or more solid electrolytes may be used together without impairing the effectiveness of the invention.
[0315] (Conductive materials and adhesives)
[0316] As the conductive material in the positive electrode active material layer 111, the materials described in the above-described (conductive materials) section can be used. Furthermore, the proportion of the conductive material in the positive electrode mixture can also be the proportion described in the above-described (conductive materials) section. Additionally, as the binder in the positive electrode, the materials described in the above-described (binder) section can be used.
[0317] (Positive current collector)
[0318] The positive current collector 112 of the positive electrode 110 can be made of the material described above (positive current collector).
[0319] One method for loading the positive electrode active material layer 111 onto the positive electrode current collector 112 is to press-form the positive electrode active material layer 111 onto the positive electrode current collector 112. Press-forming can be performed using cold pressing or hot pressing.
[0320] Alternatively, an organic solvent can be used to gelatinize a mixture of CAM, solid electrolyte, conductive material and binder to prepare a positive electrode mixture. The obtained positive electrode mixture is then coated on at least one side of the positive electrode current collector 112 and dried and pressed to fix it, thereby enabling the positive electrode active material layer 111 to be supported on the positive electrode current collector 112.
[0321] Alternatively, an organic solvent can be used to gelatinize the mixture of CAM, solid electrolyte and conductive material to prepare a positive electrode agent. The obtained positive electrode agent is then coated on at least one side of the positive electrode current collector 112 and dried and sintered, thereby enabling the positive electrode active material layer 111 to be supported on the positive electrode current collector 112.
[0322] As organic solvents that can be used in the positive electrode mixture, the same organic solvents that can be used in gelatinizing the positive electrode mixture as described above in (positive electrode current collector) can be used.
[0323] As a method for coating the positive electrode mixture onto the positive electrode current collector 112, the method described above (positive electrode current collector) can be cited as an example.
[0324] The positive electrode 110 can be manufactured using the methods listed above.
[0325] (negative electrode)
[0326] The negative electrode 120 has a negative electrode active material layer 121 and a negative electrode current collector 122. The negative electrode active material layer 121 contains a negative electrode active material. In addition, the negative electrode active material layer 121 may contain a solid electrolyte and a conductive material. The negative electrode active material, negative electrode current collector, solid electrolyte, conductive material, and binder may be those described above.
[0327] As for the method of loading the negative electrode active material layer 121 onto the negative electrode current collector 122, similar to that for the positive electrode 110, the following methods can be listed: a method based on pressure molding, a method of coating a paste-like negative electrode mixture containing the negative electrode active material onto the negative electrode current collector 122, drying and then pressing, and a method of coating a paste-like negative electrode mixture containing the negative electrode active material onto the negative electrode current collector 122, drying and then sintering.
[0328] (Solid electrolyte layer)
[0329] The solid electrolyte layer 130 has the aforementioned solid electrolyte.
[0330] The solid electrolyte layer 130 can be formed by sputtering an inorganic solid electrolyte onto the surface of the positive electrode active material layer 111 of the positive electrode 110.
[0331] Alternatively, the solid electrolyte layer 130 can be formed by coating a paste-like mixture containing a solid electrolyte onto the surface of the positive electrode active material layer 111 of the positive electrode 110 and drying it. After drying, it can be pressed and further pressurized by cold isostatic pressing (CIP) to form the solid electrolyte layer 130.
[0332] The laminate 100 can be manufactured by using a known method, such that the negative electrode 120 is laminated with the surface of the negative electrode active material layer 121 in contact with the surface of the solid electrolyte layer 130 relative to the solid electrolyte layer 130 disposed on the positive electrode 110 as described above.
[0333] The positive electrode active material for all-solid-state lithium-ion batteries with the above-described structure allows for smooth lithium-ion transfer between the positive electrode and the solid electrolyte, thereby improving battery performance.
[0334] The electrode structure described above, having the aforementioned positive electrode active material for all-solid-state lithium-ion batteries, can improve the battery characteristics of all-solid-state lithium-ion batteries.
[0335] As an aspect, the present invention also includes the following solutions.
[0336]
[12] A CAM particle for lithium secondary batteries, which is a CAM particle for lithium secondary batteries containing at least Li and Ni, wherein, when the volume magnetic susceptibility of the CAM particle for lithium secondary batteries as a whole is calculated for a plurality of particles, the modal value of the volume magnetic susceptibility in the range of 0.004 to 0.04 is 0.0043 to 0.0117.
[0337]
[13] According to
[12] , the average value of the above-mentioned volume magnetic susceptibility is 0.005 to 0.08.
[0338]
[14] CAM particles for lithium secondary batteries according to
[12] or
[13] , wherein the median value of the above-mentioned volume magnetic susceptibility is 0.0001 to 0.1.
[0339]
[15] CAM particles for lithium secondary batteries according to any one of
[12] to
[14] , wherein the standard deviation of the volume magnetic susceptibility is 0.005 to 0.1.
[0340]
[16] CAM particles for lithium secondary batteries according to any one of
[12] to
[15] , wherein the average particle size based on the number of CAM particles for lithium secondary batteries is 1.0 μm to 20 μm.
[0341]
[17] CAM particles for lithium secondary batteries according to any one of
[12] to
[16] , wherein the median value of the particle size based on the number of CAM particles for lithium secondary batteries is 1.0 μm to 20 μm.
[0342]
[18] CAM particles for lithium secondary batteries according to any one of
[12] to
[17] , wherein the standard deviation of the particle size of the number of CAM particles for lithium secondary batteries is 0.5 μm to 15 μm.
[0343]
[19] The CAM particles for lithium secondary batteries according to any one of
[12] to
[18] contain a paramagnetic body or a diamagnetic body.
[0344]
[20] The CAM particles for lithium secondary batteries according to any one of
[12] to
[19] are represented by the following composition formula (1).
[0345] Li[Li x (Ni (1-y-z-w) Co y Mn z M w ) 1-x O2 (1)
[0346] (In the formula, M is one or more elements selected from Cu, Ti, Mg, Al, W, B, Mo, Nb, Zn, Sn, Zr, Ga and V, satisfying -0.1≤x≤0.2, 0<y≤0.5, 0≤z≤0.8, 0≤w≤0.1 and y+z+w<1).
[0347]
[21] A positive electrode for a lithium secondary battery, comprising any one of
[12] to
[20] CAM particles for a lithium secondary battery.
[0348]
[22] A lithium secondary battery having the positive electrode for a lithium secondary battery as described in
[21] .
[0349] Example
[0350] Next, the present invention will be described in more detail through embodiments.
[0351] Compositional Analysis
[0352] For the compositional analysis of the CAM particles manufactured by the method described later, the obtained CAM particle powder was dissolved in hydrochloric acid and then analyzed using an ICP emission spectrometer (manufactured by Seiko Nanotechnology Co., Ltd., SPS3000).
[0353] <Methods for determining volume magnetic susceptibility>
[0354] The medium used for the measurement was 75% glycerol. The measurement temperature was room temperature (23°C). The volumetric magnetic susceptibility was calculated using the following formula. A magnetic field was applied to the CAM particles dispersed in the medium, and the moving CAM particles were image-analyzed, thereby measuring the CAM particles and the volumetric magnetic susceptibility.
[0355]
[0356] In the formula, X p X represents the volumetric magnetic susceptibility of the CAM particles. m η is the volumetric magnetic susceptibility of the medium. μ0 is the permeability of free space. B is the magnetic flux density. r is the radius of the CAM particle. v is the magnetophoretic velocity of the moving CAM particle.
[0357] Using the volumetric magnetic susceptibility values obtained for 1000 CAM particles, the mode, mean, median, and standard deviation were calculated.
[0358] <Method for determining particle size based on number>
[0359] The average particle size based on the number of CAM particles was calculated using an image analysis tool based on a particle size measuring device used in conjunction with a volume magnetic susceptibility measuring device.
[0360] The particle size measuring device used was the Nanomeasure (KNM-001) manufactured by Yamato Scientific.
[0361] The mean, median, and standard deviation were calculated using the particle size values obtained for each of 1000 CAM particles as a baseline.
[0362] Analysis of paramagnetic or diamagnetic components
[0363] The compositional analysis of CAM particles was performed using inductively coupled plasma (ICP) analysis.
[0364] The median particle size of the alumina media, based on volume, was calculated using a sieving method based on a vibrating screen device. The vibrating screen device used was a circular vibrating screen (KIC type 1200) manufactured by Xinghe Industrial Co., Ltd.
[0365] <Making of the Positive Electrode for Lithium-ion Secondary Batteries>
[0366] A paste-like positive electrode mixture was prepared by adding CAM particles, conductive material (acetylene black), and binder (PVdF) in a mass ratio of 92:5:3 (CAM particles: conductive material: binder) and kneading. N-methyl-2-pyrrolidone was used as the organic solvent in the preparation of the positive electrode mixture.
[0367] Making a Lithium Secondary Battery (Coin-Shaped Half-Battery)
[0368] The following operations were performed inside a glove box under an argon atmosphere.
[0369] The positive electrode for a lithium-ion secondary battery, prepared according to the "Preparation of Positive Electrode for Lithium-ion Secondary Batteries," was placed with its aluminum foil side down on the lower cover of a component for a coin-shaped battery R2032 (manufactured by Hosen Co., Ltd.), and a separator (a porous polyethylene membrane) was placed on top of it. 300 μL of electrolyte was then injected. The electrolyte used was a mixture in which LiPF6 was dissolved at a ratio of 1.0 mol / L in a 30:35:35 (volume ratio) mixture of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate.
[0370] Next, lithium metal was used as the negative electrode, and the negative electrode was placed on the upper side of the laminated membrane separator. The top cover was then placed on the membrane through a gasket, and the two were riveted together using a riveting machine to produce a lithium secondary battery (coin-type half-cell R2032, sometimes referred to as "half-cell" below).
[0371] [Charge / Discharge Evaluation: Initial Charge Capacity and Initial Discharge Capacity]
[0372] Using the coin-shaped lithium secondary battery prepared by the above method, the initial charge capacity and initial discharge capacity were measured by the above-described methods for measuring "initial charge capacity" and "initial discharge capacity".
[0373] Example 1
[0374] 1. Manufacturing of CAM Particles 1
[0375] Water was added to a reaction vessel equipped with a stirrer and an overflow pipe, followed by an aqueous sodium hydroxide solution to maintain the liquid temperature at 50°C.
[0376] A mixed feed solution was prepared by mixing aqueous solutions of nickel sulfate, cobalt sulfate, and manganese sulfate to achieve an atomic ratio of 85:10:5.
[0377] Next, the mixed raw material solution and an aqueous solution of ammonium sulfate as a complexing agent were continuously added to the reaction tank under stirring. Sodium hydroxide aqueous solution was added dropwise in a timely manner to bring the pH of the solution in the reaction tank to 12 (measured at a liquid temperature of 40°C), thus obtaining particles of nickel-cobalt-manganese composite hydroxide.
[0378] The particles of nickel-cobalt-manganese composite hydroxide were washed, then dehydrated and separated by centrifugation and dried at 150°C to obtain nickel-cobalt-manganese composite hydroxide 1.
[0379] Nickel-cobalt-manganese composite hydroxide 1 and lithium hydroxide monohydrate powder were weighed to a ratio of Li / (Ni+Co+Mn)=1.10.
[0380] Potassium sulfate was weighed in a molar ratio of 0.1 between potassium sulfate as an inactive flux and lithium hydroxide monohydrate powder.
[0381] Mixture 1 was obtained by mixing nickel-cobalt-manganese composite hydroxide 1, lithium hydroxide monohydrate powder and potassium sulfate in a mortar.
[0382] The resulting mixture 1 was mixed with alumina medium at a mass ratio of 5% by mass. The alumina medium contained more than 99% by mass of alumina relative to its total mass, and contained Si, K, Na, and Fe as major impurities. The median particle size of the alumina medium was 2.0 mm on a volume basis.
[0383] Then, it was fired at 820°C for 10 hours in an oxygen atmosphere.
[0384] Then, it was washed with water and dried at 760°C for 5 hours under an oxygen atmosphere. This yielded CAM particle 1 powder.
[0385] Example 2
[0386] Except for the addition of an aluminum medium containing 5% aluminum by weight to mixture 1 at a mass ratio of 15%, CAM particle powder 2 was obtained by the same method as in Example 1.
[0387] Example 3
[0388] 1. Manufacturing of CAM Particles 3
[0389] Water was added to a reaction vessel equipped with a stirrer and an overflow pipe, followed by an aqueous sodium hydroxide solution to maintain the liquid temperature at 50°C.
[0390] A mixed feed solution was prepared by mixing aqueous solutions of nickel sulfate, cobalt sulfate, and aluminum sulfate to achieve an atomic ratio of 88:9:3.
[0391] Next, the mixed raw material solution and an aqueous solution of ammonium sulfate as a complexing agent were continuously added to the reaction tank under stirring. Sodium hydroxide aqueous solution was added dropwise in a timely manner to bring the pH of the solution in the reaction tank to 12 (measured at a liquid temperature of 40°C), thus obtaining particles of nickel-cobalt-aluminum composite hydroxide.
[0392] The particles of nickel-cobalt-aluminum composite hydroxide were washed, then dehydrated and separated by centrifugation and dried at 150°C to obtain nickel-cobalt-aluminum composite hydroxide 1.
[0393] Nickel-cobalt-aluminum composite hydroxide 1 and lithium hydroxide monohydrate powder were weighed to a ratio of Li / (Ni+Co+Al)=1.10.
[0394] Mixture 2 was obtained by mixing nickel-cobalt-aluminum composite hydroxide 1 and lithium hydroxide monohydrate powder in a mortar.
[0395] The alumina medium used in Example 1 was added to the resulting mixture 2 at a mass ratio of 5% by mass, and the mixture was then mixed.
[0396] Then, it was fired at 720°C for 6 hours in an oxygen atmosphere.
[0397] Then, it was washed with water and dried at 250°C for 10 hours under a nitrogen atmosphere. This yielded CAM particle 3 powder.
[0398] Example 4
[0399] Except for the addition of an aluminum medium containing 5% aluminum by weight to mixture 2 at a weight ratio of 15%, CAM particle powder 4 was obtained by the same method as in Example 3.
[0400] Comparative Example 1
[0401] Except for the absence of any alumina medium or aluminum medium, CAM particle 5 powder was obtained by the same method as in Example 1.
[0402] Comparative Example 2
[0403] Except for the absence of either alumina medium or aluminum medium, CAM particle powder was obtained by the same method as in Example 3.
[0404]
[0405] As shown in Table 1, when comparing Examples 1 and 2 with Comparative Example 1, the first charge capacity and first discharge capacity of the Examples are higher than those of the Comparative Example.
[0406] Furthermore, when comparing Examples 3 and 4 with Comparative Example 2, the initial charge capacity and initial discharge capacity of the Examples are higher than those of the Comparative Example.
[0407] Industrial availability
[0408] According to the present invention, positive electrode active material particles for lithium secondary batteries, positive electrode for lithium secondary batteries, and lithium secondary batteries can be provided, which enable lithium ions to migrate smoothly and improve the battery characteristics of lithium secondary batteries.
[0409] Symbol Explanation
[0410] 1. Separator, 2. Positive electrode, 3. Negative electrode, 4. Electrode group, 5. Battery tank, 6. Electrolyte, 7. Top insulator, 8. Sealing body, 10. Lithium secondary battery, 21. Positive electrode lead, 31. Negative electrode lead, 100. Laminated structure, 110. Positive electrode, 111. Positive electrode active material layer, 112. Positive electrode current collector, 113. External terminal, 120. Negative electrode, 121. Negative electrode electrolyte layer, 122. Negative electrode current collector, 123. External terminal, 130. Solid electrolyte layer, 200. Outer casing, 200a. Opening, 1000. All-solid-state lithium-ion secondary battery.
Claims
1. A positive electrode active material particle for lithium secondary batteries, comprising at least Li and Ni, wherein, Having determined the overall volumetric magnetic susceptibility of a single particle of the positive electrode active material for lithium secondary batteries from multiple particles, the mode of the individual volumetric magnetic susceptibility values within the range of 0.004 to 0.04 is 0.008 to 0.
011. The average value of the volume magnetic susceptibility is 0.00960 to 0.02440. The median value of the volume magnetic susceptibility is 0.00032 to 0.01550. The standard deviation of the volumetric magnetic susceptibility is 0.01800–0.03020. The average particle size of the positive electrode active material particles used in the lithium secondary battery is 2.84 μm to 4.56 μm, based on the number of particles. The median particle size of the positive electrode active material particles used in the lithium secondary battery is 2.17 μm to 3.85 μm, based on the number of particles. The standard deviation of the particle size of the positive electrode active material particles used in the lithium secondary battery, based on the number of particles, is 1.71 μm to 3.33 μm. The positive electrode active material particles for lithium secondary batteries contain paramagnetic or diamagnetic materials.
2. The positive electrode active material particles for lithium secondary batteries according to claim 1, wherein, The average value of the volume magnetic susceptibility is 0.01000 to 0.01540.
3. The positive electrode active material particles for lithium secondary batteries according to claim 1 or 2, wherein, The median value of the volume magnetic susceptibility is 0.00840 to 0.01070.
4. The positive electrode active material particles for lithium secondary batteries according to claim 1 or 2, wherein, The standard deviation of the volume magnetic susceptibility is 0.01840 to 0.01870.
5. The positive electrode active material particles for lithium secondary batteries according to claim 1 or 2, wherein, The average particle size of the positive electrode active material particles used in the lithium secondary battery is 3.50 μm to 4.22 μm, based on the number of particles.
6. The positive electrode active material particles for lithium secondary batteries according to claim 1 or 2, wherein, The median particle size of the positive electrode active material particles used in the lithium secondary battery is 3.18 μm to 3.62 μm, based on the number of particles.
7. The positive electrode active material particles for lithium secondary batteries according to claim 1 or 2, wherein, The standard deviation of the particle size of the positive electrode active material particles used in the lithium secondary battery is 1.97 μm to 2.69 μm.
8. The positive electrode active material particles for lithium secondary batteries according to claim 1 or 2, wherein, When the overall volume magnetic susceptibility of a single particle of the positive electrode active material for lithium secondary batteries is determined for multiple particles, the modulus of the volume magnetic susceptibility in the range of 0.004 to 0.04 is 0.008 to 0.
010.
9. The positive electrode active material particles for lithium secondary batteries according to claim 1 or 2, wherein, The positive electrode active material particles for lithium secondary batteries are particles with a diamagnetic layer on the surface of lithium metal composite oxide particles, wherein the diamagnetic layer has a higher aluminum content than the lithium metal composite oxide.
10. The positive electrode active material particles for lithium secondary batteries according to claim 9, wherein, The aluminum content is 10 to 30% of the total mass of the antimagnetic layer.
11. The positive electrode active material particles for lithium secondary batteries according to claim 1 or 2, which are represented by the following compositional formula (1), Li[Li x (Ni (1-y-z-w) Co y Mr z M w ) 1-x ]O2 (1) In the formula, M is one or more elements selected from Cu, Ti, Mg, Al, W, B, Mo, Nb, Zn, Sn, Zr, Ga and V, satisfying -0.1≤x≤0.2, 0<y≤0.5, 0≤z≤0.8, 0≤w≤0.1 and y+z+w<1.
12. A positive electrode for a lithium secondary battery, comprising active material particles for a lithium secondary battery as described in any one of claims 1 to 11.
13. A lithium secondary battery having the positive electrode for a lithium secondary battery as described in claim 12.
Citation Information
Patent Citations
Non-aqueous electrolyte battery separator and lithium secondary battery
JP2000030686A
High density nickel hydroxide coprecipitated with cobalt and manganese, and method for producing the same
JP2002201028A
Bipolar battery and its control method
JP2004095400A
Compound oxide
JP2005145790A
Imaging apparatus, control method of the same, and program
JP2020072300A